The Intersection of Comparative Advertising and Trademark Laws in the United States and the European Union - Cynthia W. Sharp (Nordic Journal of Commercial Law, 2019)
United States and European Union trademark laws have common foundations in the Paris Convention for the Protection of Industrial Property and also in the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). As parties to these international agreements, both jurisdictions are obligated to adhere to certain fundamental parameters regarding trademark law and its enforcement. Despite these shared roots, a comparison of the European Court of Justice’s ruling in L’Oréal v. Bellure with the factually similar US Ninth Circuit Court of Appeals case Smith v. Chanel reveals a divergence between the US and the EU in these two jurisdictions’ construal of the interaction between trademark law and comparative advertising law. This variance reflects differences in the cultural and policy considerations behind these jurisdictions’ creation of the laws. Ultimately, however, it is due to fundamental differences in subsequent interpretations of those laws, as illustrated by diverging developments in the relevant case law. An understanding of these differences and developments can help clarify not only the reasons for their emergence, but may also help predict future directions the laws may take. This paper is divided into four main sections. Section 1 presents an overview of comparative advertising laws in the EU and the US, providing background for the case law discussion that follows. Section 2 delves further into these jurisdictions’ respective trademark and comparative advertising laws to reveal their interrelationship, the foundations upon which they are based, and the values they are intended to protect. Section 3 reviews the cases at issue in light of those laws and proposes that the divergence in laws between the EU and US stems primarily from opposing interpretations of anti-dilution laws. This divergence then triggers different interpretations regarding the way in which trademark law should intersect with comparative advertising law. Section 4 suggests that the Max Planck Institute’s Study on the Overall Functioning of the European Trade Mark System indicates that in the future, the EU laws are likely to align more closely with their US counterparts, if certain proposals made by the Institute are implemented by the European Commission.